2016
DOI: 10.4081/pb.2015.6071
|View full text |Cite
|
Sign up to set email alerts
|

Proline Content and Yield Components of Local Corn Cultivars from Kisar Island, Maluku, Indonesia

Abstract: Proline is one of amino acid that usually accumulates inside the plant cell when facing drought stress. The accumulation of proline can protect the plant cell from damage during drought. The aim of this research was to determine proline content and yield components of local corn cultivars from Kisar Island, Maluku, Indonesia. The field trial was organized using randomized block design with three replicates. Six local corn cultivars found in Kisar Island (Deep Yellow, Early Maturing Yellow, Red Blood, Rubby Bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
4
9
0
Order By: Relevance
“…Another result also reported by Sinay et al, (2015) about the proline content and yield of local corn cultivars on natural conditions in Kisar Island, which indicates that the Kuning Dalam cultivar has the highest proline content (in line with the results of greenhouse experiments, according to Sinay & Karuwal, 2014), as well as high yields such as the number of seeds per cob, the number of rows of seeds, the cob weight, the cob length, and the cob diameter.…”
Section: Resultssupporting
confidence: 69%
“…Another result also reported by Sinay et al, (2015) about the proline content and yield of local corn cultivars on natural conditions in Kisar Island, which indicates that the Kuning Dalam cultivar has the highest proline content (in line with the results of greenhouse experiments, according to Sinay & Karuwal, 2014), as well as high yields such as the number of seeds per cob, the number of rows of seeds, the cob weight, the cob length, and the cob diameter.…”
Section: Resultssupporting
confidence: 69%
“…The number of ears per plant recorded for waxy and dent Corn genotypes were similar. The number of ears per plant for grain corn was reported between 1.12 and 1.28, for waxy Corn genotypes from 1 to 3 [40,43,44]. The number of ears per plant obtained in this experiment were lower than those reported by Souvandouane et al (2010), while in harmony with the values given in the previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, some negative correlations were found between leaf proline content and relative water content (RWC), then between leaf proline content and leaf greenness, 100 grain weight and yield of maize grain, as previously reported by Mansouri‐Far et al (). Sinay et al () studied the proline content and maize yield components. They found that maize hybrids with high proline content also have the highest cob weight before and after drying, cob length, diameter, number of seeds per cob and the yield.…”
Section: Introductionmentioning
confidence: 99%